Cdc42 is an antihypertrophic molecular switch in the mouse heart - Maillet, Marjorie (American Society for Clinical Investigation, 2009)
To improve contractile function, the myocardium undergoes hypertrophic growth without myocyte proliferation in response to both pathologic and physiologic stimulation. Various membrane-bound receptors and intermediate signal transduction pathways regulate the induction of cardiac hypertrophy, but the cardioprotective regulatory pathways or effectors that antagonize cardiac hypertrophy remain poorly understood. Here we identify the small GTPase Cdc42 as a signaling intermediate that restrained the cardiac growth response to physiologic and pathologic stimuli. Cdc42 was specifically activated in the heart after pressure overload and in cultured cardiomyocytes by multiple agonists. Mice with a heart-specific deletion of Cdc42 developed greater cardiac hypertrophy at 2 and 8 weeks of stimulation and transitioned more quickly into heart failure than did wild-type controls. These mice also displayed greater cardiac hypertrophy in response to neuroendocrine agonist infusion for 2 weeks and, more remarkably, enhanced exercise-induced hypertrophy and sudden death. These pathologies were associated with an inability to activate JNK following stimulation through a MEKK1/MKK4/MKK7 pathway, resulting in greater cardiac nuclear factor of activated T cells (NFAT) activity. Restoration of cardiac JNK signaling with an Mkk7 heart-specific transgene reversed the enhanced growth effect. These results identify what we believe to be a novel antihypertrophic and protective cardiac signaling pathway, whereby Cdc42-dependent JNK activation antagonizes calcineurin-NFAT activity to reduce hypertrophy and prevent transition to heart failure.